TNF-α and IL-10 as paracrine effect of encapsulated mesenchymal stem cells coating by platelet lysate - Sibuea, Christine Verawaty; Sitanggang, Ervina Julien; Simaremare, Ade Pryta; Silaen, Rachel Teodora; Kuara , Glenessa; Samosir, Sarah Christina; Ginting, Kharnis Marsha Madora; Yana, Hiqmah Yusi; Pratama, Gita; Mutiara, Mutiara; Angeline, Wiedya Kristianti (Institute of Computer Science (IOCS), 2024)
Mesenchymal stem cells (MSCs) have been used as a cellular therapy for infectious and degenerative diseases due to their paracrine effect, immunomodulatory capability, high ability differentiation, and high plasticity. The paracrine effect of MSCs releases many growth factors and pro-inflammatory cytokines such as tumor necrosis factor-α (TNF-α) and interleukin-10 (IL-10), enabling them to modulate the immune system. Nevertheless, there are many obstacles to maintaining paracrine effects in cellular therapy due to a shortage of cellular retention. MSC encapsulation provides a favourable environment for the enhanced viability of MSCs. Platelet lysate is comprised of many growth factors that support the paracrine effect of mesenchymal stem cells (MSCs). In this study, MSCs were encapsulated within alginate, crosslinked using calcium chloride (CaCl2), and subsequently coated with platelet lysate. Encapsulated MSCs coated by platelet lysate were cultured for 21 days and analyzed for IL-10 and TNF-α levels. The findings of our study performed that TNF-α in encapsulated mesenchymal stem cells (MSCs) coated with platelet lysate increased until day 21. IL-10 was retained within the capsule and detected very in day 14. This study showed that encapsulated MSCs coated with platelet lysate affected paracrine effect TNF-α of MSC and retained IL-10 inside the capsule